(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This study examines the function of metaphorical thinking in Uzbek and English from a cognitive typological and cross-cultural standpoint. Metaphors represent human intellect and cultural worldviews in addition to being verbal expressions. Through a comparison of conceptual metaphors pertaining to time, love, and life in both languages, the study reveals how individuals interpret and communicate abstract concepts using well-known cultural imagery. The study makes the case that historical, social, and environmental variables are intimately related to variations in metaphorical systems. By including metaphor-based explanations, the results may aid English language instructors in fostering cultural competency in EFL courses.